Socio‐economic composition of low‐acuity paediatric presentation at a regional hospital emergency department. (4th June 2018) - Alele, Faith O; Callander, Emily J; Emeto, Theophilus I; Mills, Jane; Watt, Kerrianne
Abstract : Aim: Despite increasing rates of emergency department (ED) utilisation, little is known about low‐acuity presentations in children ≤5 years. The aims of the study were to estimate the proportion and cost of low‐acuity presentations in children ≤5 years presenting to the ED and to determine the relative effect of socio‐economic status (SES) on paediatric low‐acuity presentations at the ED. Methods: This is a retrospective observational study of children ≤5 years presenting to the Cairns Hospital ED over 4 years. A multivariate logistic regression model was used to assess the association between SES and low‐acuity presentations. Cost of low‐acuity presentations was calculated based on triage score and admission status, using costs obtained from the National Hospital Cost Data Collection. Results: A total of 23 086 children were included in the study, of whom 56.7% were male (mean age = 1.85 ± 1.63 years). Approximately one‐third of ED visits were low‐acuity presentations (32.4%), and low‐acuity presentations increased progressively with SES. In multivariate analysis, children from families with very high SES were twice as likely to have a low‐acuity presentation (odds ratio 2.17; 95% confidence interval, 1.66–2.85). Low‐acuity ED presentations cost the health‐care system in excess of A895 000–A1 110 000 per year. Conclusions: These findings demonstrate that a significant proportion of paediatric ED visits are of low acuity and that these visits yield a substantial cost to the health system. Further research is required regarding care givers' rationale and potentially other reasons underlying these low‐acuity ED presentations.